2013
DOI: 10.1074/jbc.m112.407635
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Highly Curved Structures in Relation to Membrane Permeabilization and Budding by the Triterpenoid Saponins, α- and δ-Hederin

Abstract: Background:The triterpenoid monodesmosidic saponins, ␣-and ␦-hederin, induced membrane permeabilization. Results: The membranous cholesterol and the sugars branched on the aglycone, hederagenin, are critical for membrane permeabilization, budding, and the change in lipid phase. Conclusion: Permeabilization and budding are dependent on the interaction of saponin with cholesterol and the molecular shape of the saponin. Significance: Induction of curvature by saponins is responsible for permeabilization and buddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 76 publications
10
108
1
Order By: Relevance
“…Triterpenoids increase cell membrane permeability by forming pore‐like channels , and a very recent report demonstrated that the saponin ( α ‐hederin) sugar chains are required to efficiently interact with sterols in the membrane for pore formation and budding. The triterpenoid aglycone, without sugar moieties, only provided poor intravesicular budding (Figure , α ‐hederin) . Cationic triterpenoids have also been described in the literature that show a detergent‐like antibacterial effect which is generated by their amine‐enriched structures (Figure , CSA) .…”
mentioning
confidence: 92%
“…Triterpenoids increase cell membrane permeability by forming pore‐like channels , and a very recent report demonstrated that the saponin ( α ‐hederin) sugar chains are required to efficiently interact with sterols in the membrane for pore formation and budding. The triterpenoid aglycone, without sugar moieties, only provided poor intravesicular budding (Figure , α ‐hederin) . Cationic triterpenoids have also been described in the literature that show a detergent‐like antibacterial effect which is generated by their amine‐enriched structures (Figure , CSA) .…”
mentioning
confidence: 92%
“…Saponaria and Gypsophila species with saporins (type I ribosome-inactivating protein, RIP-I) (Gevrenova et al, 2014;Gilabert-Oriol et al, 2016;Holmes et al, 2015;Smith et al, 2017), confirm that saponins generally interact with biological membranes in a gentle and reversible way. Although most authors link biological activity of saponins with their affinity for cholesterol (Glauert et al, 1962;Lorent et al, 2013;Schulman and Rideal, 1937;Windaus, 1909), our recent results suggest that interaction with phospholipids present in the membrane might be equally important (Orczyk and Wojciechowski, 2015;Wojciechowski et al, 2014Wojciechowski et al, , 2016.…”
Section: Introductionmentioning
confidence: 60%
“…The adjuvant activity of the QS‐21 fraction of saponins from Quillaja saponaria Molina (Fernández‐Tejada et al, ; Sanders et al, ), as well as recent results on synergistic biological activity of saponins from Saponaria and Gypsophila species with saporins (type I ribosome‐inactivating protein, RIP‐I) (Gevrenova et al, ; Gilabert‐Oriol et al, ; Holmes et al, ; Smith et al, ), confirm that saponins generally interact with biological membranes in a gentle and reversible way. Although most authors link biological activity of saponins with their affinity for cholesterol (Glauert et al, ; Lorent et al, ; Schulman and Rideal, ; Windaus, ), our recent results suggest that interaction with phospholipids present in the membrane might be equally important (Orczyk and Wojciechowski, ; Wojciechowski et al, , ).…”
Section: Introductionmentioning
confidence: 64%
“…Cholesterol, ergosterol, and stigmasterol are membrane constituents; they insert deeply in the membrane structures and affect their dynamic properties (Dufourc 2008). The structure of a triterpenic compound (Dufourc 2008;Prades et al 2011;Rodriguez et al 1997), the number of oxidized groups Pownall 2005, 2006), and the conjugation to a sugar structure (Lorent et al 2013;Hu et al 1996) are the factors that control the interaction and consequently the effects of triterpenic molecules on the membrane properties. Among the natural pentacyclic triterpenes, many reports have been published concerning the interaction with lipid membrane of lupeol (Rodriguez et al 1997;Broniatowski et al 2012a, b), betulinic acid (Broniatowski et al 2012a, b), betulin (Broniatowski et al 2012a), oleanolic, maslinic, ursolic acids (Prades et al 2011;Han et al 1997), alpha-amyrin, and taraxerol (Rodriguez et al 1997).…”
Section: Introductionmentioning
confidence: 99%